Understanding accessibility to healthcare for elderly people in Bangladesh. Issue 4 (19th May 2018) - Abdullah, J.M.; Ahmad, Mokbul Morshed; Saqib, Shahab E.
ABSTRACT: Healthcare facilities for the rising number of elderly people living in rural and semi-urban areas in Bangladesh are insufficient. This article assesses the accessibility to healthcare for elderly people living in rural and semi-urban areas. Data collection was carried out using surveys, focus group discussions, and key informant interviews, and both quantitative and qualitative tools were used in analysis. Upazila hospitals, which are geographically easily accessible for elderly people in rural and semi-urban areas, have a dearth of specialist doctors to treat their chronic diseases and lack sophisticated diagnostic facilities. It is recommended that a course on gerontology be introduced in the medical curriculum to increase the number of available geriatricians, and resources allocated for sophisticated diagnostic facilities in upazila hospitals.